Multiple regression analysis: effects of math anxiety and self-regulated learning on learning outcomes - Priharvian, Syifa Maharani; Diana, Safina Putri; Dewanti, Sintha Sih (Pusat Studi Pengembangan Pembelajaran Matematika, 2024)
Student learning outcomes are not only influenced by cognitive factors but also affective factors. This study used a research design to investigate the influence of math anxiety and self-regulated learning on student learning outcomes. The population of this study was all secondary schools in Yogyakarta. The sample used consisted of 187 female students and 127 male students in grades X, XI, and XII. Data were obtained through student learning outcomes and the distribution of affective scales to students to obtain data on math anxiety and self-regulated learning. The analysis concluded that math anxiety and self-regulated learning influence student learning outcomes. The effect of math anxiety and self-regulated learning on female students is 86.7% and on male students is 15.8%. There is a model to calculate the effect obtained based on the analysis, namely Ŷ = -9,077 + 0,455 X1 + 0,826 X2 for female students and Ŷ = 0,815 X1+ 0,480 X2 for male students.